Answer:
m(x)= 0 when X= 3
Step-by-step explanation:
2*3=6
6-6=0
For (2x-6)
3-4=-1
So -1*0=0
it can also be look at like this (0,-1)
Answer:
8.5 in
Step-by-step explanation:
You are solving for the hypotenuse right? So you would use this formula:
c = square root a^2+b^2
the c is the hypotenuse (long side of a right triangle) and a will be 4 and b will be 7.5. substitute the numbers in, solve, and you get 8.5 inches!
x = square root 4^2 + 7.5^2
x = square root 16 + 56.25
x = square root 72.25
x = 8.5 inches
The answer is 40% i hope u do well
Answer:
x = 5/3
General Formulas and Concepts:
<u>Algebra I</u>
Equality Properties
- Multiplication Property of Equality
- Division Property of Equality
- Addition Property of Equality
- Subtraction Property of Equality
Step-by-step explanation:
<u>Step 1: Define</u>
<em>Identify given.</em>
y = 3x - 2
y = 3
<u>Step 2: Solve for </u><u><em>x</em></u>
- [Equation] Substitute in <em>y</em>:
3 = 3x - 2 - [Addition Property of Equality] Add 2 on both sides:
5 = 3x - [Division Property of Equality] Divide 3 on both sides:
5/3 = x - Rewrite:
x = 5/3
∴ the value of <em>x</em> when <em>y</em> = 3 is equal to 5/3, or approximately 1.67.
---
Learn more about Algebra I: brainly.com/question/27710551
---
Topic: Algebra I
Answer:
k=0.832926
Step-by-step explanation: